2014
DOI: 10.1007/s10711-013-9947-x
|View full text |Cite
|
Sign up to set email alerts
|

Quotient categories, stability conditions, and birational geometry

Abstract: Abstract. This article deals with the quotient category of the category of coherent sheaves on an irreducible smooth projective variety by the full subcategory of sheaves supported in codimension greater than c. It turns out that this category has homological dimension c. As an application of this, we will describe the space of stability conditions on its derived category in the case c=1. Moreover, we describe all exact equivalences between these quotient categories in this particular case which is closely rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Proof. We will define mutually inverse maps, following [10,Lemma 3.6]. We start by constructing a map from right to left.…”
Section: John Calabrese and Roberto Pirisimentioning
confidence: 99%
See 1 more Smart Citation
“…Proof. We will define mutually inverse maps, following [10,Lemma 3.6]. We start by constructing a map from right to left.…”
Section: John Calabrese and Roberto Pirisimentioning
confidence: 99%
“…Diverging a little from [10], finding the precise relationship between the derived category D(X) and the birational geometry of X has been an active area of research for quite some time (see [5] for an excellent overview). We wonder if the study of the derived category of the quotients D(C c (X)), or some intermediate version of them, might help make some progress in the matter.…”
mentioning
confidence: 99%
“…(1) (X) = D b (X)/S, where S is the subcategory of complexes with cohomology supported in codimension at least two (see [40]). On the other hand, φ has a well-defined dynamical degree λ(φ).…”
Section: 2mentioning
confidence: 99%
“…We consider the triangulated category D b Coh (1) (X) defined as the quotient of the bounded derived category D b Coh(X) by the full subcategory consisting of complexes whose support has codimension at least 1 [32, Definition 3.1] (see Section 5.2). Meinhardt-Partsch [32] observed that the triangulated category D b Coh (1) (X) is closely related to the birational geometry of X and showed that the space of stability conditions on D b Coh (1) (X) behaves roughly like that on a curve. Using their results and Theorem 1.7, we can show the following.…”
mentioning
confidence: 99%